Rosiglitazone has a null association with the risk of prostate cancer in type 2 diabetes patients - Tseng, Chin-Hsiao (Frontiers in Endocrinology, 2023)
Background: This study investigated the risk of prostate cancer in ever users and never users of rosiglitazone in diabetes patients in Taiwan.The nationwide database of the National Health Insurance was used to enroll male patients who had a new diagnosis of type 2 diabetes mellitus at an age ≥ 25 years from 1999 to 2005. A total of 11,495 ever users and 11,495 never users of rosiglitazone matched on propensity score were selected and they were followed up for the incidence of prostate cancer from January 1, 2006 until December 31, 2011. Cox proportional hazard model incorporated with the inverse probability of treatment weighting using the propensity score was used to estimate hazard ratios.At the end of follow-up, incident cases of prostate cancer were found in 84 never users and 90 ever users of rosiglitazone. The calculated incidence was 173.20 per 100,000 person-years in never users and was 187.59 per 100,000 person-years in ever users. The overall hazard ratio (95% confidence intervals) for ever versus never users was 1.089 (0.808-1.466). The hazard ratios were 0.999 (0.643-1.552) for the first tertile (< 672 mg), 1.147 (0.770-1.709) for the second tertile (672-3584 mg) and 1.116 (0.735-1.695) for the third tertile (> 3584 mg) of cumulative dose. Sensitivity analyses consistently showed a null association between rosiglitazone and prostate cancer risk.Conclusions: Rosiglitazone has a null effect on the risk of prostate cancer.